Research Needs for High-Level Waste Stored in Tanks and Bins at U.S. Department of Energy Sites: Environmental Management Science Program - National Research Council (The National Academies Press, 2001)
The United States Department of Energy (DOE) has approximately 400 million liters (100 million gallons) of liquid high-level waste (HLW) stored in underground tanks and approximately 4,000 cubic meters of solid HLW stored in bins. The current DOE estimate of the cost of converting these liquid and solid wastes into stable forms for shipment to a geological repository exceeds $50 billion to be spent over several decades (DOE, 2000). The Committee on Long-Term Research Needs for Radioactive High-Level Waste at Department of Energy Sites was appointed by the National Research Council (NRC) to advise the Environmental Management Science Program (EMSP) on a long-term research agenda addressing the above problems related to HLW stored in tanks and bins at DOE sites.
Keywords: Environment and Environmental Studies; Engineering and Technology

Improving the Quality of Long-Term Care - Institute of Medicine (The National Academies Press, 2001)
Among the issues confronting America is long-term care for frail, older persons and others with chronic conditions and functional limitations that limit their ability to care for themselves. Improving the Quality of Long-Term Care takes a comprehensive look at the quality of care and quality of life in long-term care, including nursing homes, home health agencies, residential care facilities, family members and a variety of others. This book describes the current state of long-term care, identifying problem areas and offering recommendations for federal and state policymakers. Who uses long-term care? How have the characteristics of this population changed over time? What paths do people follow in long term care? The committee provides the latest information on these and other key questions. This book explores strengths and limitations of available data and research literature especially for settings other than nursing homes, on methods to measure, oversee, and improve the quality of long-term care. The committee makes recommendations on setting and enforcing standards of care, strengthening the caregiving workforce, reimbursement issues, and expanding the knowledge base to guide organizational and individual caregivers in improving the quality of care.
Keywords: Health and Medicine

Aquifer Storage and Recovery in the Comprehensive Everglades Restoration Plan: A Critique of the Pilot Projects and Related Plans for ASR in the Lake Okeechobee and Western Hillsboro Areas - National Research Council (The National Academies Press, 2001)
Aquifer storage and recovery (ASR) is a process by which water is recharged through wells to an aquifer and extracted for beneficial use at some later time from the same wells. ASR is proposed as a major water storage component in the Comprehensive Everglades Restoration Plan (CERP), developed jointly by the U.S. Army Corps of Engineers (USACE) and the South Florida Water Management District (SFWMD). The plan would use the Upper Floridan aquifer (UFA) to store as much as 1.7 billion gallons per day (gpd) (6.3 million m3/day) of excess surface water and shallow groundwater during wet periods for recovery during seasonal or longer-term dry periods, using about 333 wells. ASR represents about one-fifth of the total estimated cost of the CERP. Aquifer Storage and Recovery in the Comprehensive Everglades Restoration Plan examines pilot project from the perspective of adaptive assessment, i.e., the extent to which the pilot projects will contribute to process understanding that can improve design and implementation of restoration project components. This report is a critique of the pilot projects and related studies.
Keywords: Environment and Environmental Studies

Global Air Quality: An Imperative for Long-Term Observational Strategies - National Research Council (The National Academies Press, 2001)
The National Research Council's Committee on Atmospheric Chemistry (NRC/CAC) was established to serve as a focal point for NRC activities on issues related to atmospheric chemical change and its impacts on air quality, climate, stratospheric ozone depletion, and other related issues. The committee consists of 12 members with expertise covering the areas of tropospheric and stratospheric chemistry; urban/regional air pollution; modeling of climate, chemistry, and atmospheric dynamics; in situ and remote sensing observational systems; and interfaces of science and public policy.This CAC study was motivated by a concern that, in the coming decades, dramatic increases in global population and urbanization levels, as well as changes in global climate, may significantly affect air quality over large regions of the globe. The charge to the committee was to examine the linkages among regional/ global changes in atmospheric composition, climate change, and air quality.
Keywords: Environment and Environmental Studies

Improving Operations and Long-Term Safety of the Waste Isolation Pilot Plant: Final Report - National Research Council (The National Academies Press, 2001)
The Waste Isolation Pilot Plant (WIPP) is a deep underground mined facility for the disposal of transuranic waste resulting from the nation's defense program. Transuranic waste is defined as waste contaminated with transuranic radionuclides with half-life greater than 20 years and activity greater than 100 nanocuries per gram. The waste mainly consists of contaminated protective clothing, rags, old tools and equipment, pieces of dismantled buildings, chemical residues, and scrap materials. The total activity of the waste expected to be disposed at the WIPP is estimated to be approximately 7 million curies, including 12,900 kilograms of plutonium distributed throughout the waste in very dilute form. The WIPP is located near the community of Carlsbad, in southeastern New Mexico. The geological setting is a 600-meter thick, 250 million-year-old saltbed, the Salado Formation, lying 660 meters below the surface. The National Research Council (NRC) has been providing the U.S. Department of Energy (DOE) scientific and technical evaluations of the WIPP since 1978. The committee's task is twofold: (1) to identify technical issues that can be addressed to enhance confidence in the safe and long-term performance of the repository and (2) to identify opportunities for improving the National Transuranic (TRU) Program for waste management, especially with regard to the safety of workers and the public. This is the first full NRC report issued following the certification of the facility by the U.S. Environmental Protection Agency (EPA) on May 18, 1998. An interim report was issued by the committee in April 2000 and is reproduced in this report. The main findings and recommendations from the interim report have been incorporated into the body of this report. The overarching finding and recommendation of this report is that the activity that would best enhance confidence in the safe and long-term performance of the repository is to monitor critical performance parameters during the long pre-closure phase of repository operations (35 to possibly 100 years). Indeed, in the first 50 to 100 years the rates of important processes such as salt creep, brine inflow (if any), and microbial activity are predicted to be the highest and will be less significant later. The committee recommends that the results of the on-site monitoring program be used to improve the performance assessment for recertification purposes. These results will determine whether the need for a new performance assessment is warranted. For the National TRU Program, the committee finds that the DOE is implementing many of the recommendations of its interim report. It is important that the DOE continue its efforts to improve the packaging, characterization, and transportation of the transuranic waste.
Keywords: Environment and Environmental Studies

Research and Development on a Salt Processing Alternative for High-Level Waste at the Savannah River Site - National Research Council (The National Academies Press, 2001)
The U.S. Department of Energy (DOE) is nearing a decision on how to process 30 million gallons of high-level radioactive waste salt solutions at the Savannah River Site in South Carolina to remove strontium, actinides, and cesium for immobilization in glass and eventual shipment to a geologic repository. The department is sponsoring research and development (R&D) work on four alternative processes and plans to use the results to make a downselection decision in a June 2001 time frame. The DOE requested that the National Research Council help inform this decision by addressing the following charge: evaluate the adequacy of the criteria that will be used by the department to select from among the candidate processes under consideration; evaluate the progress and results of the research and development work that is being undertaken on these candidate processes; and assess whether the technical uncertainties have been sufficiently resolved to proceed with downsizing the list of candidate processes. Responses to the last two points are provided in this report. Research and Development on a Salt Processing Alternative for High-Level Waste at the Savannah River Site focuses exclusively on the technical issues related to the candidate processes for radionuclide removal from high-level waste salt solutions at SRS. The committee's interim report served as a response to the first point of this charge, and may be read in Appendix B. In that report, the committee found that DOE's proposed criteria are an acceptable basis for selecting among the candidate processes under consideration, but that the criteria should not be implemented in a way that relies on a single numerical "total score."
Keywords: Environment and Environmental Studies

Science and Technology for Environmental Cleanup at Hanford - National Research Council (The National Academies Press, 2001)
The Hanford Site was established by the federal government in 1943 as part of the secret wartime effort to produce plutonium for nuclear weapons. The site operated for about four decades and produced roughly two thirds of the 100 metric tons of plutonium in the U.S. inventory. Millions of cubic meters of radioactive and chemically hazardous wastes, the by-product of plutonium production, were stored in tanks and ancillary facilities at the site or disposed or discharged to the subsurface, the atmosphere, or the Columbia River. In the late 1980s, the primary mission of the Hanford Site changed from plutonium production to environmental restoration. The federal government, through the U.S. Department of Energy (DOE), began to invest human and financial resources to stabilize and, where possible, remediate the legacy of environmental contamination created by the defense mission. During the past few years, this financial investment has exceeded $1 billion annually. DOE, which is responsible for cleanup of the entire weapons complex, estimates that the cleanup program at Hanford will last until at least 2046 and will cost U.S. taxpayers on the order of $85 billion. Science and Technology for Environmental Cleanup at Hanford provides background information on the Hanford Site and its Integration Project,discusses the System Assessment Capability, an Integration Project-developed risk assessment tool to estimate quantitative effects of contaminant releases, and reviews the technical elements of the scierovides programmatic-level recommendations.
Keywords: Environment and Environmental Studies

Reefscape: Reflections on the Great Barrier Reef - Rosaleen Love (The National Academies Press, 2001)
Located off Australia's eastern coast, the Great Barrier Reef is one of the wonders of the natural world. The diversity of life is simply incredible. It is also the ideal environment for coral, making it a diver's paradise. Indeed, some 200 million tourists visit the reef each year. Looking beyond the sheer beauty of this place, we learn, too, that it is a region rich in history, the setting for fateful shipwrecks and exotic Aboriginal myths. Australian writer Rosaleen Love explores the reef from all these angles, allowing us to see this stunning geography anew. Part travelogue, part eco-history, Reefscape represents multiple views of the reef - through the eyes of mariners, pearl divers, naturalists, filmmakers, pirates, industrialists, and tourists alike- painting a fascinating portrait of a unique locale. Told in a reflectively poetic voice, Love writes evocatively of the ecological, and geological significance of the reef. Woven throughout is the intriguing history of the area. This twofold approach provides a rich perspective on the reef an ecosystem as well as a natural resource for its inhabitants. By recounting both tales, Reefscape provides a window on the past and foreshadows the future of this extraordinary environment. Reefscape will illuminate the meaning of the human encounter with nature. It will inspire delight in the imagination and spirit of all who yearn for the transcendence of turquoise waters.
Keywords: Explore Science; Earth Sciences

No Time to Lose: Getting More from HIV Prevention - Institute of Medicine (The National Academies Press, 2001)
The United States has spent two productive decades implementing a variety of prevention programs. While these efforts have slowed the rate of infection, challenges remain. The United States must refocus its efforts to contain the spread of HIV and AIDS in a way that would prevent as many new HIV infections as possible. No Time to Lose presents the Institute of Medicine’s framework for a national prevention strategy.
Keywords: Health and Medicine

Mountains of Madness: A Scientist's Odyssey in Antarctica - John Long (The National Academies Press, 2001)
This extraordinary book is the first-person account of John Long's two unforgettable "summers" on the southern continent. Told in a highly accessible and entertaining style, Mountains of Madness is the account of his three-month long fossil hunt. As the story unfolds, we learn of both the highs of scientific discovery as well as the grueling yet essential routines that must be practiced every day just to stay alive in one of the harshest environments on our planet. Alternating with the author's wonder at the intense beauty of his surroundings are his immense frustration and boredom that stem from being completely at the mercy of the elements. Throughout the course of the expedition, danger is never far off in this inhospitable land. Despite having been trained in the art of building snow caves and practiced in the skill of traversing glaciers, Long tells of two brushes with death in just one afternoon. The hair-raising escape from a deep crevasse is fraught with tension-only to be followed by yet another encounter with sudden disaster when the crash of an avalanche buries Long deep in the snow.
Keywords: Earth Sciences

Good Seeing: A Century of Science at the Carnegie Institution of Washington, 1902-2002 - James Trefil; Margaret Hindle Hazen; Timothy Ferris (The National Academies Press, 2001)
Good Seeing presents a readable, inspiring history of the Carnegie Institution of Washington, from its founding in 1902, through the emergence of "big science" after World War II, to the institution's role in addressing the major science questions of the 21st century. Authors James Refil and Margaret Hindle Hazen open their narrative with the story of Andrew Carnegie, a Scottish bobbin boy who used his ingenuity to build a fortune in industrial America—and then turned his energy to giving that fortune away. The book then goes on to chronicle the groundbreaking work accomplished by the various Carnegie departments, tracing their growth and change as the frontiers of science expanded through the decades. And it looks at Carnegie's influence on the mechanisms of science funding, the institution's early support of ecology, and the building of the world's leading astronomical observatories. The authors offer fascinating glimpses into the lives of science giants Barbara McClintock, George Ellery Hale, Edwin Hubble, Vera Rubin, Alfred Kidder—and the legendary Vannevar Bush, Institution President from 1939-1955. Lavishly illustrated with historical photos and drawings, this celebration of the Carnegie Institution's century of discovery will be a delightful read for scientists, science advocates, and students of American science leadership.
Keywords: Explore Science; Biography and Autobiography

The Role of Environmental NGOs: Russian Challenges, American Lessons: Proceedings of a Workshop - National Research Council (The National Academies Press, 2001)
An NRC committee was established to work with a Russian counterpart group in conducting a workshop in Moscow on the effectiveness of Russian environmental NGOs in environmental decision-making and prepared proceedings of this workshop, highlighting the successes and difficulties faced by NGOs in Russia and the United States.
Keywords: Policy for Science and Technology

NAEP Reporting Practices: Investigating District-Level and Market-Basket Reporting - National Research Council (The National Academies Press, 2001)
At the request of the Department of Education, the National Research Council formed the Committee on NAEP Reporting Practices to address questions about the desirability, feasibility, and potential impact of implementing these reporting practices. The committee developed study questions designed to address issues surrounding district-level and market-basket reporting.
Keywords: Education

Twenty-Third Symposium on Naval Hydrodynamics - National Research Council (The National Academies Press, 2001)
"Vive la Revolution!" was the theme of the Twenty-Third Symposium on Naval Hydrodynamics held in Val de Reuil, France, from September 17-22, 2000 as more than 140 experts in ship design, construction, and operation came together to exchange naval research developments. The forum encouraged both formal and informal discussion of presented papers, and the occasion provides an opportunity for direct communication between international peers. This book includes sixty-three papers presented at the symposium which was organized jointly by the Office of Naval Research, the National Research Council (Naval Studies Board), and the Bassin d'Essais des Carènes. This book includes the ten topical areas discussed at the symposium: wave-induced motions and loads, hydrodynamics in ship design, propulsor hydrodynamics and hydroacoustics, CFD validation, viscous ship hydrodynamics, cavitation and bubbly flow, wave hydrodynamics, wake dynamics, shallow water hydrodynamics, and fluid dynamics in the naval context.
Keywords: Math, Chemistry, and Physics

American Hazardscapes: The Regionalization of Hazards and Disasters - Susan L. Cutter (The National Academies Press, 2001)
Barrier islands. Flood plains. Earthquake faults. Sometimes the environment poses threats to our well being, yet many of us continue to choose to live in risky or dangerous places. And on top of the “knowns” are the other, more hidden hazards related to environmental contamination that pose equally serious threats to our health and well being. But where are these places and what types of hazards are found there? American Hazardscapes examines the risks associated with living and owning property in diverse regions across the United States, offering dual perspectives: that of the geographer and that of the social science hazards researcher. The book summarizes what we already know about regional patterns of hazard events and losses during the previous three decades and goes further to shed light on the nature of the events themselves and their impact on society. Written for the relocating citizen and the policy maker alike, American Hazardscapes presents a regional ecology of disaster-prone or disaster-resistant states. It also offers thoughts on what local, state, and federal managers need to do to meet the challenge of reducing hazard losses in the next century.
Keywords: Explore Science; Earth Sciences; Conflict and Security Issues

Eclipse: The Celestial Phenomenon That Changed the Course of History - Duncan Steel (The National Academies Press, 2001)
Whether interpreted as an auspicious omen or a sentinel of doom, eclipses have had a profound effect upon our cultural development. Throughout recorded history, they have evoked consternation, fear, and dread—as well as awe and wonderment. Ancient peoples were clearly disconcerted by them. The Romans marked pivotal battles with the Greeks by references to an eclipse. The date of the crucifixion of Jesus Christ has been derived by using biblical mentions of an eclipse. Perhaps most famously, Christopher Columbus extorted much-needed foodstuffs from some increasingly unfriendly native hosts by purporting to demonstrate the wrath of his most powerful God when he accurately predicted a lunar eclipse. The pattern that eclipses follow—a cycle, called the saros—was actually calculated thousands of years ago. However, it is only with the help of modern computers that we have been able to analyze and appreciate the data. Eclipses provide unique opportunities for today’s scientists to study such contrasting phenomena as the upper layers of the sun, the slowdown of our planet’s spin rate, and the effects of celestial events on human psychology. In Eclipse, Duncan Steel expertly captures our continuing fascination with all manner of eclipses—including the familiar solar and lunar varieties and other kinds involving stars, planets, asteroids, and comets as well as distant galaxies and quasars. Steel helps us see that, in astronomical terms, eclipses are really rather straightforward affairs. Moving beyond the mysticism and the magic, the science of eclipses is revealed.
Keywords: Explore Science; Space and Aeronautics

America Becoming: Racial Trends and Their Consequences: Volume II - National Research Council (The National Academies Press, 2001)
The 20th Century has been marked by enormous change in terms of how we define race. In large part, we have thrown out the antiquated notions of the 1800s, giving way to a more realistic, sociocultural view of the world. The United States is, perhaps more than any other industrialized country, distinguished by the size and diversity of its racial and ethnic minority populations. Current trends promise that these features will endure. Fifty years from now, there will most likely be no single majority group in the United States. How will we fare as a nation when race-based issues such as immigration, job opportunities, and affirmative action are already so contentious today? In America Becoming, leading scholars and commentators explore past and current trends among African Americans, Hispanics, Asian Americans, and Native Americans in the context of a white majority. This volume presents the most up-to-date findings and analysis on racial and social dynamics, with recommendations for ongoing research. It examines compelling issues in the field of race relations, including: Race and ethnicity in criminal justice. Demographic and social trends for Hispanics, Asian Americans, and Native Americans. Trends in minority-owned businesses. Wealth, welfare, and racial stratification. Residential segregation and the meaning of "neighborhood." Disparities in educational test scores among races and ethnicities. Health and development for minority children, adolescents, and adults. Race and ethnicity in the labor market, including the role of minorities in America's military. Immigration and the dynamics of race and ethnicity. The changing meaning of race. Changing racial attitudes. This collection of papers, compiled and edited by distinguished leaders in the behavioral and social sciences, represents the most current literature in the field. Volume 1 covers demographic trends, immigration, racial attitudes, and the geography of opportunity. Volume 2 deals with the criminal justice system, the labor market, welfare, and health trends, Both books will be of great interest to educators, scholars, researchers, students, social scientists, and policymakers.
Keywords: Behavioral and Social Sciences

Analysis of Engineering Design Studies for Demilitarization of Assembled Chemical Weapons at Pueblo Chemical Depot - National Research Council (The National Academies Press, 2001)
The Program Manager for Assembled Chemical Weapons Assessment (PMACWA) of the Department of Defense (DOD) requested the National Research Council (NRC) to assess the engineering design studies (EDSs) developed by Parsons/Honeywell and General Atomics for a chemical demilitarization facility to completely dispose of the assembled chemical weapons at the Pueblo Chemical Depot in Pueblo, Colorado. To accomplish the task, the NRC formed the Committee on Review and Evaluation of Alternative Technologies for Demilitarization of Assembled Chemical Weapons: Phase II (ACW II Committee). This report presents the results of the committee's scientific and technical assessment, which will assist the Office of the Secretary of Defense in selecting the technology package for destroying the chemical munitions at Pueblo. The committee evaluated the engineering design packages proposed by the technology providers and the associated experimental studies that were performed to validate unproven unit operations. A significant part of the testing program involved expanding the technology base for the hydrolysis of energetic materials associated with assembled weapons. This process was a concern expressed by the Committee on Review and Evaluation of Alternative Technologies for Demilitarization of Assembled Chemical Weapons (ACW I Committee) in its original report in 1999 (NRC, 1999). The present study took place as the experimental studies were in progress. In some cases, tests for some of the supporting unit operations were not completed in time for the committee to incorporate results into its evaluation. In those cases, the committee identified and discussed potential problem areas in these operations. Based on its expertise and its aggressive data-gathering activities, the committee was able to conduct a comprehensive review of the test data that had been completed for the overall system design. This report summarizes the study.
Keywords: Environment and Environmental Studies; Math, Chemistry, and Physics

Space Studies Board Annual Report 2000 (The National Academies Press, 2001)

Climate Change Science: An Analysis of Some Key Questions - National Research Council (The National Academies Press, 2001)
The warming of the Earth has been the subject of intense debate and concern for many scientists, policy-makers, and citizens for at least the past decade. Climate Change Science: An Analysis of Some Key Questions, a new report by a committee of the National Research Council, characterizes the global warming trend over the last 100 years, and examines what may be in store for the 21st century and the extent to which warming may be attributable to human activity.
Keywords: Earth Sciences; Environment and Environmental Studies